Integrins are required for tissue organization and restriction of neurogenesis in regenerating planarians - Seebeck, Florian; März, Martin (Development, 2017)
Skip to Next Section: Tissue regeneration depends on proliferative cells and on cues that regulate cell division, differentiation, patterning and the restriction of these processes once regeneration is complete. In planarians, flatworms with high regenerative potential, muscle cells express some of these instructive cues. Here, we show that members of the integrin family of adhesion molecules are required for the integrity of regenerating tissues, including the musculature. Remarkably, in regenerating β1-integrin RNAi planarians, we detected increased numbers of mitotic cells and progenitor cell types, as well as a reduced ability of stem cells and lineage-restricted progenitor cells to accumulate at wound sites. These animals also formed ectopic spheroid structures of neural identity in regenerating heads. Interestingly, those polarized assemblies comprised a variety of neural cells and underwent continuous growth. Our study indicates that integrin-mediated cell adhesion is required for the regenerative formation of organized tissues and for restricting neurogenesis during planarian regeneration.
Published online February 28, 2017
Gesehen am 25.06.2018